Perancangan Aplikasi Penyewaan Alat Berat berbasis Web pada PT. Indotruck Citra Pramata Jambi (LPPM Universitas Dinamika Bangsa, 2017)
PT. Indotruck Citra Pramata Jambi is one of the companies located in the Jambi where system rental heavy equipment still use help help book , agenda , microsoft excel and microsoft word .So that problems occur that is difficult to increase the number of reservations in rental heavy equipment significantly , the slow the dissemination of information to rental and the way rental heavy equipment in detail , and the availability of and price heavy equipment that will leased and the obstacles in data processing rental heavy equipment in recording data customers , calculation data rental heavy equipment and payment. Hence , this study aims to give solution to the problem by offering application rental heavy equipment use of language programming PHP and a database MySWL where writer do system development with the methods waterfall and used the model system the unified model language use use case diagram ,activity diagram ,class diagram and flowchart, diagram. The new system produce outputs that can manage and display data heavy equipment, data rental heavy equipment ,data payment heavy equipment and data forum